Предмет: Математика,
автор: wolf128
упростите выражение 6,3х-4-3(7,2х+0,3) и найдите его значение при х=2/3
Ответы
Автор ответа:
0
6,3x - 4 - 3( 7,2x + 0,3 ) = 6,3x - 4 - 21,6x + 0,9 = - 15,3x - 3,1
X = 2/3
- ( 153/10 )•( 2/3 ) - 3,1 = - ( 51/5 ) - 3,1 = - 10,2 - 3,1 = - 13,3
X = 2/3
- ( 153/10 )•( 2/3 ) - 3,1 = - ( 51/5 ) - 3,1 = - 10,2 - 3,1 = - 13,3
Похожие вопросы
Предмет: Химия,
автор: vladimirlasin434
Предмет: Физкультура и спорт,
автор: Аноним
Предмет: Математика,
автор: 4xrhh6x99v
Предмет: Биология,
автор: Никита878